High use of over-the-counter analgesic; possible warnings of reduced quality of life in adolescents - a qualitative study - Skarstein, Siv (BMC Nurs, 2016)
BACKGROUND: Use of over-the-counter analgesics among adolescents has increased markedly. High consumption of over-the-counter analgesics among adolescents is associated with frequent pain, lower self-esteem, reduced sleep, lower educational ambition, binge drinking, higher caffeine consumption, and part-time employment. Knowledge about life experiences of adolescents who frequently use over-the-counter analgesics may be useful to prevent health problems. The purpose of the study was to increase knowledge about adolescents who suffer from frequent pain and have a high consumption of over-the-counter analgesics. METHODS: A qualitative study, employing one-on-one, in-depth interviews using a thematic interview guide. Data were collected in Norway in 2013–2014. Three boys and sixteen girls; aged 14–16 years, who continuously consumed over-the-counter analgesics were recruited from ten high schools in urban and suburban districts. Candidate participants were excluded if they were medically diagnosed with an acute or chronic illness, requiring extended use of over-the-counter analgesics within the last year. The interviews were taped, transcribed and analysed as text according to Kvale’s three contexts of interpretation: self-understanding, common sense and theory. RESULTS: All participants disclosed unresolved physical and psychosocial distress characterized as pain. Frequent pain from various body parts made everyday life challenging. Methods of pain self-appraisal and over-the-counter analgesics use often mimicked maternal patterns. Participants reported being raised under unpredictable circumstances that contributed to long lasting family conflicts and peer-group problems. Participants wanted to feel appreciated and to be socially and academically successful. However, pain reduced their ability to manage everyday life, hampered experienced possibilities for success, and made social settings difficult. CONCLUSIONS: Childhood experiences influence how adolescents experience pain and use over-the-counter analgesics. Coping with difficult situations or attempting to mask symptoms with over-the-counter analgesics can perpetuate and amplify underlying problems. High consumption of over-the-counter analgesics and frequent pain may be warning signs of adolescents with possible health threatening conditions and reduced quality of life. These adolescent might be in need of support from school nurses and General Practitioners. This study identifies new perspectives that may lead to novel approaches to identify, guide, and support adolescents with frequent pain and high consumption of over-the-counter analgesics.